Analysis of Factors Affecting the Depression and Quality of Life in the Family Taking Care of Dementia Patients (Medico Legal Update, 2020)
Background/Objectives: This study was intended to identify the factor having influence on the stress, depression and the quality of life in the family who care the patient with dementia.Method/Statistical Analysis: For this study, raw data were requested to Korea Centers for Disease Control and Prevention and among them, the data for 150,802 citizens of 45 years or older in D Metropolitan City were analyzed. For the analysis, the statistical software R program was used and the significance level was 0.05.Findings: Out of the factors having influence on the family who are cohabitating with the patient with dementia, the factors having influence on the quality of life were age, benefit of basic living security, lifelong drinking, days of medium level of physical activity, diabetes, arthritis, subjective oral health level, subjective health level, experience of depression, etc..Improvements/Applications: This study was intended to provide the basic data to develop the programs for the health improvement and the health education of the family who care the patient with dementia